Perception on Pneumococcal Vaccination towards Infants among the Community in Selayang, Selangor: A Qualitative Study - Afiqah Zulkifili; Nadiah S. Azehar; Sarah N. Zamalolaily; Zulhairie R. Zulfaka; Sabariah A. Hamid (Asian Journal of Medicine & Health Sciences, 2022)
Background: Pneumococcal disease is the leading cause of death in children under the age of five. Pneumococcal conjugate vaccines (PCVs) have been shown to be highly efficient in decreasing morbidity and mortality from Invasive Pneumococcal Disease (IPD). This study aims to explore the awareness and perceptions on acceptance, benefits and alternative solutions on pneumococcal vaccination towards infants among parents in Selayang. Methods: A qualitative study was conducted among nine participants in Selayang who aged more than 20 years old. This study used purposive sampling and in-depth interviews of individual respondents using a semi structured interview guide. All interviews were audio-recorded, transcribed verbatim and checked. Thematic approach was used to analyze the data. Results: The result showed that PCV awareness was fairly good and was generally accepted among most participants, as a protection mechanism for children, and because of recommendations from healthcare and service provided by the government. Meanwhile, three out of nine participants refused to take vaccines due to external barriers, personal belief and vaccine-related reasons. The finding of perceptive benefits towards PCV was summarized as prevention of pneumonia, enhanced immunity level, and control progression of the disease. Three alternative solutions to prevent pneumonia were identified: nutritious diet and supplements, complementary medicine and exercise, and natural approach to health and immunity. Conclusion: Parents had multiple perceptions about PCV towards infants. It is crucial for healthcare professionals to recognise and address these concerns when consulting parents to increase awareness on PCV.